Effect of Improvised Instructional Materials on Students’ Academic Achievement in Mathematics in Bayelsa State, Nigeria - Erepamowei Ayibakuro Diri; Elisha Abel Udo (Scientia Publica Media, 2025)
This study examined the effect of improvised instructional materials on students’ academic achievement in mathematics. The purpose of this study geared towards determining the impact of improvised instructional materials on students’ academic achievement in mathematics. The study was directed by two research questions and two hypotheses. Determining the effect of improvised instructional materials on junior secondary school (JSS) students’ academic achievement in mathematics and investigate the effect of improvised instructional materials on the academic achievement of students in mathematics to gender. Quasi-experimental design was employed in this study. The population included 1,546 JSS II students from 34 public secondary schools in Ogbia Local Government Area, Bayelsa State, with a sample of 80 students selected through simple random sampling from two schools, one serving as the experimental group and the other as the control group. Each group consisted of 40 students (22 males and 18 females). The Mathematics Achievement Test (MAT), developed by the researcher, was used as the research instrument, and a test-retest procedure established its reliability at 0.77 using Pearson Product Moment Correlation Coefficient (PPMCC). Mean and standard deviation were used to answer the research questions and t-test analysis applied to test the null hypotheses at a 0.05 significance level. The findings indicated a significant difference in the academic achievement of mathematics students, suggesting that improvised instructional materials were a more effective learning method in contrast to the traditional method. This implies that improvised instructional material plays a vital role in improving mathematics students’ academic achievement. Therefore, it was recommended that mathematics teachers incorporate improvised materials in their teaching and that the government provide funding to support this initiative.